La réalisation des actes de parole dans les textes usuels sur l’exemple des annonces matrimoniales - Otulak-Komenda, Monika (Studia Romanica Posnaniensia, 2017)
They are representatives (a glorification and doubts), directives (a request, questions, an encouragement and a temptation, an invitation, an advice, a prohibition), commissives (a promise and an obligation), expressives (a thanks, a greeting) and declarations. Thanks to them reaching the goal of persuasion: coming into a contact between sender and recipient becomes possible.